2021
DOI: 10.1002/jsfa.11061
|View full text |Cite
|
Sign up to set email alerts
|

Early identification of Aspergillus spp. contamination in milled rice by E‐nose combined with chemometrics

Abstract: BACKGROUND Rice grains can be contaminated easily by certain fungi during storage and in the market chain, thus generating a risk for humans. Most classical methods for identifying and rectifying this problem are complex and time‐consuming for manufacturers and consumers. However, E‐nose technology provides analytical information in a non‐destructive and environmentally friendly manner. Two‐feature fusion data combined with chemometrics were employed for the determination of Aspergillus spp. contamination in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Moreover, the performance parameters of the network, i.e., the values of accuracy, precision, recall, and specificity, were 0.999, 0.994, 0.999, and 0.099, respectively, and the values of AUC and F were also 0.997 and 0.994. These results are consistent with the results obtained by other researchers [63][64][65][66]. Ghasemi-Varnamkhasti, et al [67] used an electronic nose to determine the freshness of strawberries when they were packaged in different polymers with a high classification accuracy using the SVM method.…”
Section: Svm Resultssupporting
confidence: 90%
“…Moreover, the performance parameters of the network, i.e., the values of accuracy, precision, recall, and specificity, were 0.999, 0.994, 0.999, and 0.099, respectively, and the values of AUC and F were also 0.997 and 0.994. These results are consistent with the results obtained by other researchers [63][64][65][66]. Ghasemi-Varnamkhasti, et al [67] used an electronic nose to determine the freshness of strawberries when they were packaged in different polymers with a high classification accuracy using the SVM method.…”
Section: Svm Resultssupporting
confidence: 90%
“…In another study conducted by Zhou, Fan, Tan, Peng, Cai and Zhang [ 12 ] to predict the amount of linalool in Osmanthus perfume, using an electronic nose, R2 for the PCR and MLR methods was reported at 0.736 and 0.895, respectively, and the RMSE was reported at 3.98 and 10.10, respectively. Gu, et al [ 33 ] investigated the contamination of milled rice with an electronic nose based on the PLSR and SVM models and reported accuracies of 0.913–0.877 and 0.983–0.924, respectively. Du, et al [ 34 ] evaluated the ability of an electronic nose to identify the SSC and TA of red meat kiwi fruit using the PLSR and SVM models; their results were R2 > 0.90 and R2 = 0.99, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…They were able to correctly classify the oil samples with 100% accuracy using the C-SVM method. Gorji-Chakespari et al [ 33 ] reported 99% accuracy in classifying Damascus rose essential oil by the SVM method. Karami, Rasekh, and Mirzaee-Ghaleh [ 8 ] also found 98% and 97% accuracies in training and validating SVM methods with linear kernel functions for oil oxidation detection.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that both HS-GC-IMS and E-Nose methods could be used to detect the contamination level of polished rice fungus, and HS-GC-IMS fingerprint combined with chemometrics could serve as an alternative method for high sensitivity detection. In addition, Gu et al (2021) also studied E-nose combined with an extreme learning machine (ELM) to clearly distinguish the fungus species of four groups of rice contaminated with mildew for two days, with an accuracy Aspergillus species infected with rice was demonstrated by GC-MS. The performance of the monitoring model based on ELM and genetic algorithm optimized support vector machine (GA-SVM) (R 2 = 0.924-0.983) is better than that of PLSR (R 2 = 0.877-0.913).…”
Section: Aspergillus Spp and Penicillium Sppmentioning
confidence: 99%